PERANCANGAN KNOWLEDGE MANAGEMENT SYSTEM BERBASIS WEBSITE PADA SEKOLAH MENENGAH ATAS XYZ - Septianudin, Septianudin; Nurmiati, Evy (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2022)
This research discusses the design of Knowledge Management System at SMA XYZ. This Knowledge Management seeks to improve the learning process at this time where at this time teaching and learning activities are carried out online due to the COVID-19 pandemic. The method in designing the Knowledge Management System at SMA XYZ uses the Knowledge Management System Life method, because this method is a method that can be used to support the analysis process, identify knowledge resources, design verification and validation of Knowledge Management Systems, implement Knowledge Management Systems and evaluate systems. developed. The purpose of this research is to help teachers and students in the learning process so that teaching and learning activities can be done anywhere. The results obtained in this study are the design of the Knowledge Management System at SMA XYZ which can be used by teachers and students. Keywords: Knowledge Management System, E-Learning, Knowledge Management System Life Cycle